The value of electron microscopy in the diagnosis of renal disease - Żurawski, Jakub; Woźniak, Aldona; Salwa-Żurawska, Wiesława (Journal of Medical Science, 2016)
In the literature of recent years there are few publications on the importance of research in electron-microscopic pathomorphological diagnosis of kidney disease. The most important, which is diagnosed only on the basis of these studies are: minimal change disease, assessment of mesangial cell proliferation as well as the differentiation of the types of membranoproliferative  glomerulonephritis, fibrillary glomerulonephritis, lupus nephritis, thin basement membrane disease, Alport syndrome, hemolytic-uremic syndrome. This report presents the most characteristic features of the ultrastructure allowing for diagnosis of these diseases.